A Parallel Comparison Method of Early Gastric Cancer: The Light Transmission-Assisted Pathological Examination of Specimens of Endoscopic Submucosal Dissection - Chen, Guangyong; Xu, Rui; Yue, Bing; Jia, Mei; Li, Peng; Ji, Ming; Zhang, Shutian (Frontiers in Oncology, 2021)
Objective It is always challenging to diagnose and characterize early gastric cancer surrounded by noncancerous mucosa, including the malignant diagnosis and extent and depth of the lesions. Therefore, we developed a light transmission-assisted pathological examination to diagnose and characterize early gastric cancer. Here, we performed a parallel comparison between the light transmission-assisted pathological examination under endoscopy and the histological examination for the diagnosis of early gastric cancer. Methods First, the endoscopic submucosal dissection (ESD) specimen was first placed on the surface of the light-emitting diode lamp to observe the mucosal surface structure and blood vessels. Second, the sliced and embedded tissue strips were cut into 3-µm sections for hematoxylin and eosin staining. Third, the histopathology of each section was projected onto a macroscopic image. Finally, the macroscopic and microscopic changes in the ESD specimens observed under endoscopy were compared. Seventy cases of early gastric adenocarcinoma were diagnosed and characterized using this new method. Results Using the conventional pathological method, the demarcation line of the lesions was seen in 40 of 70 (57.1%) cases. Furthermore, no surface structure or microvascular changes were observed in any of the cases. Based on the light transmission-assisted pathological examination, 58 of 70 (82.9%) cases presented clear edges of neoplastic and non-neoplastic epithelia, with a classifiable surface structure (88.6%) and microvascular type (78.8%). Conclusions This pilot method provided a practical bridge between endoscopic and pathological examinations. Compared to the histological examination, the light transmission-assisted pathological examination was an easier and more precise way to match the in vivo endoscopic observation and in vitro pathological examination.